Road surface pavement repair material and road surface pavement repair method

By optimizing the composition of pavement repair materials, including cement, synthetic resin, particulate matter and additives, the problem of pavement repair materials in the prior art being long and unable to effectively repair wear areas is solved, and a fast and effective pavement repair effect is achieved.

JP2025058703APending Publication Date: 2025-04-09TOOYOO MATERAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023168806
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing pavement repair materials require a lot of time and labor when filling pavement cracks, and cannot effectively repair pavement wear and need to be processed separately.

Method used

A pavement repair material containing cement, synthetic resin, particulate matter and additives is used. The ratio of cement to resin of the material and the particle size distribution are optimized to improve the workingability of the material and the seam filling capacity while reducing dry hardness and shrinkage.

Benefits of technology

This material can quickly and easily fill road cracks and effectively repair road wear, reducing the time and labor of the repair process and improving the repair efficiency and effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058703000001_ABST
    Figure 2025058703000001_ABST
Patent Text Reader

Abstract

To provide road surface pavement repair material capable of easily repairing cracks and restoring a road surface.SOLUTION: A road surface pavement repair material includes synthetic resin of 50 to 250 pts.mass (in terms of nonvolatile content), and aggregate of 100 to 500 pts.mass based on cement of 100 pts.mass. The aggregate has a largest particle diameter of 2.0 mm or less and comprises coarse aggregate and fine aggregate, wherein the coarse aggregate is silica sand with a median diameter (d50) of 1.0 to 0.4 mm, and the fine aggregate is kansui sand with a median diameter (d50) of 0.2 to 0.1 mm, and the ratio of the coarse aggregate to the fine aggregate is 80:20 to 40:60. A coating-form repair material derived from the road surface pavement repair material penetrates into cracks formed in a road surface 1 to evenly coat the entire road surface 1, and to form a repair cover coat 11 through curing of the repair material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The technical field of the present specification relates to a road surface pavement repair material that restores a paved road surface, and a road surface pavement repair method using the road surface pavement repair material. [Background technology]

[0002] A paved road surface is worn down by the traffic of vehicles, and cracks may occur due to the application of impacts and vibrations. As a road surface repair material for repairing cracks that have occurred on the road surface, Patent Document 1 describes a road surface pavement repair material consisting of a mixture of asphalt emulsion and resin, Patent Document 2 describes a mortar composition for repairing road surface pavement consisting of aggregate and binder, and Patent Document 3 describes a road surface pavement repair material consisting of aggregate with an adhesive layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-193667 A [Patent Document 2] JP 2018-100503 A [Patent Document 3] JP 2021-165470 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, repairing road surfaces using conventional road surface repair materials requires filling cracks in the road surface with the road surface repair material, which is time-consuming. In addition, repairing road surfaces using conventional road surface repair materials cannot repair worn areas, and a separate repair process is required for worn areas.

[0005] The problem that the technology of this specification aims to solve has been made in consideration of the above-mentioned points, and has the objective of providing a road surface pavement repair material that can easily repair cracks and restore the road surface. [Means for solving the problem]

[0006] The road surface pavement repair material according to the embodiment of the present specification is a road surface pavement repair material containing cement, synthetic resin, aggregate and additives, The synthetic resin is contained in an amount of 50 to 250 parts by mass (based on non-volatile content) and the aggregate is contained in an amount of 100 to 500 parts by mass relative to 100 parts by mass of the cement, The aggregate has a maximum particle size of 2.0 mm or less and is composed of coarse aggregate and fine aggregate. The coarse aggregate is silica sand having a median diameter (d50) of 1.0 to 0.4 mm, and the fine aggregate is Kansui sand having a median diameter (d50) of 0.2 to 0.1 mm, The ratio of the coarse aggregate to the fine aggregate is 80:20 to 40:60.

[0007] According to the road surface pavement repair material of the embodiment, the ratio of cement, synthetic resin, and aggregate can provide excellent workability, and since the maximum particle diameter of the aggregate contained in the road surface pavement repair material is 2.0 mm or less, it can penetrate into cracks that occur in the road surface, so the entire road surface can be easily coated. In addition, the road surface pavement repair material can reduce drying (hardening) shrinkage of the road surface pavement repair material due to the composition ratio of coarse aggregate and fine aggregate, and since the fine aggregate is cold water sand that is easily compatible with water, the strength of the repair coating formed by the road surface pavement repair material hardening can be increased. In other words, the road surface pavement repair material of the embodiment can easily repair cracks and restore the road surface.

[0008] In addition, the above-mentioned road surface pavement repair material is a two-material road surface pavement repair material consisting of a main material and a mixture liquid, The main material contains at least the cement and the aggregate, The mixture contains at least the synthetic resin, The synthetic resin may be a synthetic resin emulsion having water as a dispersion medium.

[0009] This allows the use of a general-purpose synthetic resin emulsion as the synthetic resin for the road surface repair material.

[0010] In the above road surface repair material, the admixture may contain a coloring pigment.

[0011] This makes it easy to match the color of the road surface repair material and to check the match.

[0012] Here, the road surface pavement repair method of the embodiment includes a filling step of filling a crack in a road surface with a powder-based one-material road surface pavement repair mortar composition; A coating process of coating the road surface including the cracks filled with the powder-based one-component road surface pavement repair mortar composition with the road surface pavement repair material; The present invention is characterized by having the following.

[0013] According to this method, cracks in the road surface are filled with a powder-based single-component road surface pavement repair mortar composition that has little hardening shrinkage, thereby suppressing differences in unevenness caused by shrinkage that arise from differences in the thickness of the road surface pavement repair material coating.

[0014] In the above road surface pavement repair method, the cracks filled with the powdery single-component road surface pavement repair mortar composition in the filling step may have a depth of 10 mm or more.

[0015] This makes it possible to reduce the number of cracks that need to be filled with the powder-based single-component road surface pavement repair mortar composition, thereby improving the work efficiency of road surface pavement repair. Effect of the Invention

[0016] According to the present invention, cracks can be easily repaired and the road surface can be restored. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a cross-sectional image of a road surface repaired using a road surface repair material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The road surface pavement repair material according to the embodiment of this specification and the road surface pavement repair method using this road surface pavement repair material will be described below. Note that the scope of the present invention is not limited to the scope disclosed in the embodiment. The meanings of each term in this specification and the claims are as follows.

[0019] There are two types of "road surface pavement repair materials": one-material type "road surface pavement repair materials" and two-material type "road surface pavement repair materials". The one-material type "road surface pavement repair materials" are composed of a powder main material, and the two-material type "road surface pavement repair materials" are composed of a powder main material and a liquid admixture. The one-material type "road surface pavement repair materials" are made into a repair material that can be applied to the road surface 1 by mixing the powder main material with clean water (mixing water). The two-material type "road surface pavement repair materials" are made into a repair material that can be applied to the road surface 1 by mixing the powder main material with a liquid admixture. The repair material hardens to become a repair coating 11 (Figure 1). In addition, the "average particle size" in this specification and the claims means the cumulative distribution 50 vol% (median diameter (d50)) obtained by the JIS standard sieve (JIS Z 8801-1:2019).

[0020] The road surface repair material of the embodiment contains cement, synthetic resin, aggregate, and additives. The aggregate contained in the road surface repair material has a median diameter (d50) of 0.1 to 1.0 mm and a maximum particle diameter of 2.0 mm or less, and the additives include a thickener, a coloring pigment, a hardening retarder, or a hardening accelerator.

[0021] The road surface pavement repair material is applied to a rough road surface 1 to form a repair coating 11 on the road surface 1. In particular, by applying the repair material to a road surface that has been worn, roughened, and scraped, the entire road surface 1 is covered with the repair coating 11, which repairs cracks, suppresses the generation of flying stones and noise, and restores the road surface to the appearance of a newly constructed pavement.

[0022] Cement can be used as long as it generates cement hydrate, and Portland cement specified in JIS R 5210:2019 (ordinary Portland cement, early strength Portland cement, ultra early strength Portland cement, moderate heat Portland cement, low heat Portland cement, sulfate resistant Portland cement, ordinary Portland cement (low alkali type), early strength Portland cement (low alkali type), ultra early strength Portland cement (low alkali type), moderate heat Portland cement (low alkali type), low heat Portland cement (low alkali type), sulfate resistant Portland cement (low alkali type)), or cement that does not fall under JIS but is equivalent to JIS R 5210:2019 (for example, ultra rapid hardening cement (Super Jet Cement (manufactured by Pacific Cement Corporation)), rapid hardening cement (instant rapid hardening cement (manufactured by Toyo Materan Co., Ltd.)), foreign Portland cement, etc.) can be used. In another embodiment, early strength Portland cement, extra early strength Portland cement, extra rapid hardening cement, or rapid hardening cement, which are excellent in early strength development, can be used, and in yet another embodiment, extra rapid hardening cement or rapid hardening cement can be used. Note that Portland cement also includes white Portland cement, which is made white by reducing black components (chromium (Cr2O3), manganese (Mn2O3), iron (Fe2O3), etc.) from Portland cement.

[0023] The synthetic resin in the embodiment is a raw material that imparts flexibility to the repair coating 11 formed from the road surface pavement repair material, and is a synthetic resin that can be mixed with cement. A synthetic resin emulsion or a re-emulsified powdered resin using water as a dispersion medium can be used.

[0024] When a synthetic resin emulsion is used as the synthetic resin, the road surface repair material can be a two-material type material consisting of a main material whose main components are cement and aggregates, and a liquid admixture whose main component is synthetic resin emulsion. If the additive is in powder form, it can be mixed into the main material, and if the additive is in liquid form, it can be mixed into the liquid admixture. When a re-emulsified powder resin is used as the synthetic resin, the road surface repair material can be a one-material type material consisting of the main material. In the case of a one-material type material, the additive can be selected to be in powder form.

[0025] The synthetic resin emulsion may be one that is usually mixed with an inorganic binder such as cement, and examples of such synthetic resin emulsions that can be used include vinyl carboxylate resins such as vinyl acetate resin, ethylene vinyl acetate resin, vinyl propionate resin, and vinyl versatate resin; acrylic resins such as methyl (meth)acrylate resin, ethyl (meth)acrylate resin, methyl (meth)acrylate resin, ethyl (meth)acrylate resin, butyl (meth)acrylate resin, 2-ethylhexyl (meth)acrylate resin, acrylonitrile resin, and methacrylonitrile resin; acrylic-styrene resins which are copolymers of acrylic resin and styrene resin; urethane resin, epoxy resin, alkyd resin, phenol resin, vinyl chloride resin, polypropylene resin, polyethylene resin, polystyrene resin, and modified resins thereof. As the synthetic resin emulsion, commercially available products can be used, such as Mowinyl (manufactured by Japan Coating Resins Co., Ltd.), Acronal (manufactured by BASF Ltd.), Pegal (High Pressure Gas Industries Co., Ltd.), Tomac (E-Tech Co., Ltd.), and Lipotex (Lion Specialty Chemicals Co., Ltd.).

[0026] The re-emulsified powder resin is a powder resin obtained by spray-drying a polymer emulsion, and is re-emulsified to an emulsion state by adding water. Examples of the re-emulsified powder resin include those described in Polymer Dispersions for Cement Mixtures and Re-emulsified Powder Resins (JIS A 6203:2015). Depending on the resin composition, the re-emulsified powder resin may be vinyl acetate / Veova-based, vinyl acetate / ethylene-based, vinyl acetate / acrylic-based, styrene / acrylic-based, acrylic-based, or vinyl acetate copolymer-based. Acrylic-based or styrene / acrylic-based resins, which have excellent water resistance, are preferably used. Commercially available re-emulsified powder resins may be used, such as Movinyl Powder (manufactured by Japan Coating Resins Co., Ltd.), Sumikaflex (Sumika Chemtex Co., Ltd.), Acronal (manufactured by BASF Ltd.), and ELOTEX (Celanese Japan Co., Ltd.).

[0027] The content of the synthetic resin in the road surface pavement repair material can be 50 to 250 parts by mass in terms of non-volatile content per 100 parts by mass of cement. This is because the repair coating 11 formed from the road surface pavement repair material can be made flexible and can be made to follow the vibrations and impacts that the road surface 1 receives due to vehicle traffic. If the content of the synthetic resin in the road surface pavement repair material is less than 50 parts by mass per 100 parts by mass of cement, the repair coating 11 may become hard and may easily develop defects such as cracks. On the other hand, if the content exceeds 250 parts by mass, the effect of making the repair coating 11 follow the vibrations and impacts may reach a plateau, and the expensive synthetic resin may be excessively contained, which may be uneconomical. In another embodiment, the content of the synthetic resin in the road surface pavement repair material can be 70 to 200 parts by mass per 100 parts by mass of cement, and in yet another embodiment, it can be 80 to 150 parts by mass.

[0028] The glass transition temperature (Tg) of the synthetic resin can be -30 to 30°C. This is because the repair coating 11 formed from the road surface pavement repair material can be made flexible and can follow the vibration and impact that the road surface 1 receives due to the traffic of vehicles. If the glass transition temperature of the synthetic resin is less than -30°C, the repair coating 11 formed from the road surface pavement repair material becomes soft and sticky, and may adhere to the tires of passing vehicles and peel off from the road surface 1. On the other hand, if the glass transition temperature exceeds 30°C, the repair coating 11 becomes hard and may easily cause defects such as cracks in the repair coating 11. In another embodiment, the glass transition temperature of the synthetic resin can be -20 to 20°C, and in yet another embodiment, it can be -10 to 10°C. The glass transition temperature (Tg) of the synthetic resin can be adjusted by changing the type and ratio of monomers used in the synthetic resin.

[0029] The aggregate is added to the road surface pavement repair material for the purposes of increasing the strength of the repair coating 11 formed from the road surface pavement repair material, as an extender, and adjusting the workability of the road surface pavement repair material as a paint-type repair material. Examples of aggregate that can be used include crushed stone, silica sand, kansui stone (crushed limestone), serben (crushed sanitary ware), blast furnace slag powder, and fly ash. In another embodiment, silica sand and kansui stone, which are inexpensive and easily available, can be used.

[0030] The content of aggregate in the road surface pavement repair material can be 100 to 500 parts by mass relative to 100 parts by mass of cement. This is because the road surface pavement repair material can be excellent in workability. If the content of aggregate in the road surface pavement repair material is less than 100 parts by mass, the workability is poor and expensive synthetic resin is used in large amounts, which may be uneconomical. On the other hand, if the content of aggregate exceeds 500 parts by mass, the content ratio of binder (cement and synthetic resin) is relatively small, the workability is poor, and the strength of the repair coating 11 formed from the road surface pavement repair material may be insufficient. In another embodiment, the content of aggregate in the road surface pavement repair material can be 125 to 350 parts by mass relative to 100 parts by mass of cement, and in yet another embodiment, it can be 150 to 250 parts by mass.

[0031] The average particle size (median size (d50)) of the aggregate can be 0.1 to 1.0 mm, and the maximum particle size of the aggregate can be 2.0 mm or less. This is because the road surface pavement repair material containing aggregate can enter cracks that have occurred in the road surface 1, and the anchor effect can increase the adhesion of the road surface pavement repair material to the road surface 1. If the average particle size of the aggregate is less than 0.1 mm, the road surface pavement repair material can enter cracks that have occurred in the road surface 1, but the fluidity of the road surface pavement repair material may be poor, and painting workability may be poor. On the other hand, if the average particle size of the aggregate exceeds 1.0 mm, there will be a relatively large number of coarse particles, making it difficult to fill cracks that have occurred in the road surface 1, and there is a risk that the adhesion of the road surface pavement repair material to the road surface 1 may be poor.

[0032] The aggregate can be a combination of coarse aggregate and fine aggregate, with the average particle size (median size (d50)) of the coarse aggregate being 0.4 to 1.0 mm, the average particle size of the fine aggregate being 0.1 to 0.2 mm, and the mass ratio of the coarse aggregate to the fine aggregate being coarse aggregate:fine aggregate=80:20 to 40:60. This is because it is possible to reduce the drying (hardening) shrinkage of the road surface pavement repair material and to increase the fluidity of the road surface pavement repair material. In another embodiment, the average particle size of the coarse aggregate can be 0.7 to 1.0 mm, the average particle size of the fine aggregate can be 0.1 to 0.2 mm, and the mass ratio of the coarse aggregate to the fine aggregate can be 80:20 to 60:40.

[0033] The coarse aggregate can be silica sand and the fine aggregate can be Kansui sand. The fine aggregate can be Kansui sand, which is easily mixed with water, and this increases the strength of the repair coating 11 formed by the hardening of the road surface repair material.

[0034] In addition to cement, synthetic resin and aggregate, additives such as thickeners, coloring pigments, setting retarders, hardening accelerators, film-forming agents, chelating agents, defoamers and water-reducing agents can be added to the road surface repair material.

[0035] A thickener is an additive that adjusts the viscosity and stickiness of a road surface pavement repair material and prevents the road surface pavement repair material from drying out by being added to the road surface pavement repair material. Examples of thickeners that can be added include methyl cellulose (MC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), hydroxyethyl methyl cellulose (HEMC), polyvinyl alcohol (PVA), bentonite, and the like.

[0036] The color pigment is an additive that imparts color to the repair coating 11 formed from the road surface pavement repair material by adding it to the road surface pavement repair material. The color pigment can be, for example, white; titanium oxide, zinc oxide, black; carbon black, red; red iron oxide, quinacridone, blue; cobalt blue, phthalocyanine blue, yellow; nickel titanium yellow, monoazo yellow, etc., depending on the color. The color pigment can be added to the road surface pavement repair material by uniformly dispersing the powdered color pigment in the main material. Also, if the color pigment is dispersed in a solvent such as water, it can be added to the road surface pavement repair material by mixing it with a mixing liquid. By mixing the color pigment with the mixing liquid, the color pigment immediately develops color, making it easy to adjust the color of the road surface pavement repair material and check the color adjustment.

[0037] The setting retarder is an additive that delays the setting time of cement, and examples of such additives include citric acid, tartaric acid, and gluconic acid. The hardening accelerator is an additive that accelerates the setting time of cement, and examples of such additives include lithium sulfate and calcium nitrite. If necessary, the setting retarder or hardening accelerator can be added to the road surface pavement repair material to adjust the setting time of the road surface pavement repair material to 30 to 60 minutes.

[0038] Film-forming aids are additives that lower the film-forming temperature of synthetic resins, such as Texanol and butyl cellosolve. Chelating agents are additives that sequester metal ions, such as calcium ions and iron ions, such as EDTA. Defoamers are additives that adjust the amount of bubbles in road surface pavement repair materials. Water-reducing agents are additives that increase the fluidity of road surface pavement repair materials without increasing the amount of water added.

[0039] The road surface repair material can be manufactured by mixing the raw materials for the one-component road surface repair material or the main material of the two-component road surface repair material using a mixer such as a paddle mixer, Nauta mixer, ribbon mixer, conical screw mixer, Henschel mixer, etc. The mixture for the two-component road surface repair material can be manufactured by mixing the raw materials for the two-component road surface repair material using a mixer such as a single-axis dissolver, twin-axis dissolver, butterfly dissolver, etc.

[0040] Next, a road surface pavement repair method using the road surface pavement repair material of the embodiment will be described. The road surface pavement repair method of the embodiment includes a filling step of filling a crack that has occurred on a road surface 1 with a powdery one-material type road surface pavement repair mortar composition 12, and a coating step of coating the road surface 1 including the crack that has been filled with the powdery one-material type road surface pavement repair mortar composition 12 with the road surface pavement repair material of the embodiment.

[0041] The filling step is a step of filling cracks occurring on the road surface 1 with a powder-based single-component road surface pavement repair mortar composition 12. Before the filling step, the road surface 1 to be coated is cleaned.

[0042] The powdered single-material road surface pavement repair mortar composition 12 used to fill the cracks may be, for example, a mortar composition for road surface pavement repair described in JP 2018-100503 A, which is the applicant of the present application, a watering batch, a miracle batch, an asphalt crack repair material, Hosonur SUPER (manufactured by Toyo Material Co., Ltd.), or the like.

[0043] The cracks filled with the powdered one-material road surface pavement repair mortar composition 12 can have a depth of 10 mm or more. By limiting the depth of the cracks, it is possible to suppress the occurrence of unevenness due to the thinning of the road surface pavement repair material that has entered the cracks, and it is also possible to limit the number (area) of cracks to be filled, thereby improving the efficiency of the repair work. If the depth of the cracks to be filled is less than 10 mm, the number (area) of cracks to be filled will be large, and there is a risk that the efficiency of the repair work cannot be improved. In another embodiment, the depth of the cracks filled with the powdered one-material road surface pavement repair mortar composition 12 can be 20 mm or more. Note that fine cracks that are less than this depth are filled and repaired with the road surface pavement repair material in the painting process.

[0044] The filling step can be omitted. If the filling step is omitted, when deep cracks (e.g., 20 mm or more deep) are filled with the road surface pavement repair material of the embodiment, there is a risk that unevenness occurring on the road surface 1 due to thinning of the road surface pavement repair material will become noticeable. Note that, if unevenness occurs on the road surface 1 due to thinning of the road surface pavement repair material, the occurrence of unevenness can be suppressed by applying the road surface pavement repair material again.

[0045] The coating process is a step of coating the road surface pavement repair material of the embodiment over the entire surface of the road surface 1, including the cracks filled with the powder-based single-component road surface pavement repair mortar composition 12, as shown in FIG.

[0046] Before the painting process, the road surface pavement repair material is made into a paint to be used as a repair material. When the road surface pavement repair material is a one-component material, about 80% of the specified amount of mixing water is put into a mixing container, and while stirring the mixing water with a hand mixer, the one-component road surface pavement repair material is gradually added to the mixing container and stirred. While checking the paint viscosity, the remaining 20% ​​of the mixing water is added to the paint while stirring in an increased or decreased amount to adjust the viscosity. When the road surface pavement repair material is a two-component material, the mixture is put into a mixing container, and while stirring the mixture with a hand mixer, the main material of the two-component road surface pavement repair material is gradually added to the mixing container and stirred. While checking the paint viscosity, adjustment water is added as necessary to adjust the viscosity.

[0047] The viscosity of the repair material (pavement repair material in the form of paint) can be 2 to 200 dPa·s. This is because the repair coating 11 formed from the repair material can be formed normally, and the repair material can be easily coated on the road surface 1, which is the surface to be painted. If the viscosity of the repair material is less than 2 dPa·s, the cement and aggregate contained in the repair material may settle and separate, causing defects in the repair coating 11 formed from the repair material. On the other hand, if the viscosity of the repair material exceeds 200 dPa·s, the fluidity of the repair material may be poor, and the painting efficiency may be poor. In another embodiment, the viscosity of the repair material can be 5 to 100 dPa·s, and in yet another embodiment, it can be 10 to 50 dPa·s.

[0048] The repair material is spread on the road surface 1 using a rubber rake or a plastering trowel. Since the viscosity of the repair material is low, the repair material penetrates into cracks that have occurred on the road surface 1 and is evenly applied over the entire road surface 1, and a repair coating 11 is formed as the repair material hardens. Therefore, the road surface pavement repair material of the embodiment can easily repair cracks and restore the road surface 1. By adding a setting retarder or hardening accelerator to the repair material, the setting time is adjusted to 30 to 60 minutes, which ensures a usable time and shortens the time for traffic restrictions.

[0049] By applying a repair material to the road surface 1, particularly to a road surface that has been worn, roughened, scraped, and uneven, the road surface 1 entirely covered with the repair coating 11 is prevented from generating flying stones and noise, and also has the feel of a newly constructed pavement. EXAMPLES

[0050] The road surface pavement repair material of the embodiment is made by making paints of road surface pavement repair materials with different mixtures, applying the paint-formed road surface pavement repair material to the surface of an asphalt plate of 30 cm length x 30 cm width with a rubber spatula to a thickness of 0.5 mm (wet state), curing (air temperature: 23 ± 2°C, relative humidity: 50 ± 5%, period: 2 weeks) to create a test specimen, and performing the evaluation (test) described below. Note that in the evaluations described below, × means that some of the evaluation items are not met, and does not mean that the example is out of the scope of the example.

[0051] Finishability The finish was evaluated by the quality of the road surface repair material that had been made into a paint when the test specimens were made. The surface was evaluated as ◯ if the surface was finished smoothly, △ if slight coating spots or air bubble marks were visible on the surface, and × if significant coating spots or air bubble marks were visible on the surface.

[0052] separability Separability was evaluated by evaluating the water separation property of the repair material after it was made into a paint. The samples were rated as follows: those in which no separation of moisture was observed were marked with an O; those in which some separation of moisture was observed but no abnormalities in workability or finish were observed were marked with a Δ; and those in which separation of moisture was observed and abnormalities in workability or finish were observed were marked with an X.

[0053] hardenability The curing property was evaluated by touching the repair coating 11 60 minutes after application of the repair material. The repair coating 11 was rated as ◯ when it was not felt to be sticky and did not deform when touched with a finger, as △ when it was felt to be sticky but did not deform when touched with a finger, and as × when it was felt to be sticky and did deform when touched with a finger.

[0054] Adhesion The adhesive strength of the test specimen after curing was measured using a Construction Research Institute adhesive strength tester. The adhesive strength was 0.7 N / mm 2 Above 0.4N / mm 2 Above 0.7N / mm 2 Less than 0.4N / mm 2 The results were evaluated as × when the value was less than 0.05.

[0055] flexibility Flexibility was measured in accordance with 7.26 Elongation Test of Architectural Finish Coating Materials (JIS A 6909:2014). Elongation of 10% or more was evaluated as ○, 5% or more but less than 10% as △, and less than 5% as ×.

[0056] color The color of the repair coating 11 that had been applied to the test specimen and hardened was visually confirmed. The repair coating 11 was evaluated as being darker than the asphalt plate before painting, with an O being rated, and as being lighter with an X being rated.

[0057] cost The cost was evaluated as follows: road surface repair materials whose cost was equal to or less than that of Water Sprinkler Batches (manufactured by Toyo Materan Co., Ltd.) were rated as ◯, and those whose cost exceeded that of Water Sprinkler Batches were rated as ×.

[0058] The composition of the road surface repair material and the performance evaluation results are shown in Tables 1 and 2. The composition of the road surface repair material is shown as a mass ratio (in a wet state) including volatile matter (excluding the resin non-volatile matter content).

[0059] [Table 1]

[0060] [Table 2] Some of the names of raw materials in the table are abbreviated. The raw materials used are listed below in parentheses with their general names or raw material names.

[0061] Rapid hardening cement (instant rapid hardening cement (manufactured by Toyo Matheran Co., Ltd.)) Ultra-fast hardening cement (Super Jet Cement (manufactured by Taiheiyo Cement Corporation)) Coarse aggregate (silica sand No. 5 (average particle size (d50): approx. 0.50mm)) Fine aggregate (calcium carbonate powder (average particle size (d50): approx. 0.12 mm)) Powder Em (Re-emulsifiable powder resin (non-volatile content: 95%, Tg: -10°C)) Powder color pigment (carbon black) MC (methylcellulose thickener) PVA (polyvinyl alcohol thickener) Retardant (citric acid-based retardant) AcEm (acrylic resin emulsion for cement mixing (non-volatile content: 45%, Tg: -10℃)) AcStEm (Acrylic styrene resin emulsion for cement mixing (non-volatile content: 50%, Tg: 0℃)) Color pigment (carbon black) Clean water (tap water) These were commercially available products.

[0062] (Test Examples 1 to 22) Test Examples 1 to 11 and 14 to 22 are working examples, and Test Examples 12 and 13 are comparative examples.

[0063] Test Examples 3, 5 to 11, 16, 19 and 21 (hereinafter referred to as Test Example 3, etc.) were excellent in finish, separation, curing, adhesion, flexibility, color and cost.

[0064] Test Example 1 was slightly inferior in flexibility compared to Test Example 3 and the like. This is presumed to be due to the low resin non-volatile content. Test Example 2 was slightly inferior in hardening compared to Test Example 3 and the like. This is presumed to be due to the low cement content overall. Test Example 4 was inferior in finish and separation compared to Test Example 3 and the like. This is presumed to be due to the low paint viscosity.

[0065] Test Example 12 was inferior in finish, separation, and hardening properties compared to Test Example 3, etc. This is presumably due to the fact that the cement content was low overall and the paint viscosity was low. Test Example 13 was inferior in flexibility and cost compared to Test Example 3, etc. This is presumably due to the fact that the aggregate content was low and the resin non-volatile content was low.

[0066] Test Example 14 was slightly inferior in flexibility compared to Test Example 3, etc. This is presumed to be due to the low content of non-volatile resin. Test Example 15 was inferior in finish, curing, and cost compared to Test Example 3, etc. This is presumed to be due to the high content of non-volatile resin and the paint viscosity being too high. Test Example 17 was inferior in curing and cost compared to Test Example 3, etc. This is presumed to be due to the high content of non-volatile resin. Test Example 18 was inferior in flexibility compared to Test Example 3, etc. This is presumed to be due to the low content of non-volatile resin. Test Example 20 was inferior in color compared to Test Example 3, etc. This is presumed to be due to the low content of color pigment. Test Example 22 was inferior in finish compared to Test Example 3, etc. This is presumed to be due to the viscosity of the re-emulsified powder resin, since a re-emulsified powder resin was used. [Explanation of symbols]

[0067] 1...road surface, 11...repair coating, 12...powder-based single-component mortar composition for repairing road surface pavement.

Claims

1. A road surface repair material containing cement, synthetic resin, aggregate and additives, The synthetic resin is contained in an amount of 50 to 250 parts by mass (based on non-volatile content) and the aggregate is contained in an amount of 100 to 500 parts by mass relative to 100 parts by mass of the cement, The aggregate has a maximum particle size of 2.0 mm or less and is composed of coarse aggregate and fine aggregate. The coarse aggregate is silica sand having a median diameter (d50) of 1.0 to 0.4 mm, and the fine aggregate is Kansui sand having a median diameter (d50) of 0.2 to 0.1 mm, The road surface repair material is characterized in that the ratio of the coarse aggregate to the fine aggregate is 80:20 to 40:

60.

2. A two-material road surface repair material consisting of a main material and a mixing liquid, The main material contains at least the cement and the aggregate, The mixture contains at least the synthetic resin, 2. The road surface repair material according to claim 1, characterized in that the synthetic resin is a synthetic resin emulsion using water as a dispersion medium.

3. 3. The road surface repair material according to claim 2, wherein the admixture contains a coloring pigment.

4. A filling step of filling a crack in a road surface with a powder-based one-material road surface pavement repair mortar composition; A coating process of coating the road surface including the cracks filled with the powder-based one-component road surface pavement repair mortar composition according to any one of claims 1 to 3; A road surface pavement repair method comprising the steps of:

5. 5. The road surface pavement repair method according to claim 4, wherein in the filling step, the crack portion filled with the powder-based single-component road surface pavement repair mortar composition has a depth of 10 mm or more.

Citation Information

Patent Citations

  • Mortar composition for paved road surface repair and method for paved road surface repair

    JP2018100503A

  • Repair method of asphalt paved roads

    JP2018193667A

  • Road surface pavement repairing material, manufacturing method of road surface pavement repairing material, and road surface pavement repairing method

    JP2021165470A